Evaluation of Behavior of 13X Zeolite Modified with Transition Metals for Catalytic Applications - Elena. David (Bioinorganic Chemistry and Applications)
This work was intended to develop catalysts based on 13X zeolite modified with transition metals for catalytic applications. In this regard, 13X zeolite was modified by loading of transition metals such as Fe, Co, Cu and various types of catalysts such as Fe-, Co-, Cu-, Fe-Co-, Fe-Cu-, and Co-Cu/13X zeolite were obtained. To prepare these catalysts, the wet impregnation method and metallic precursors were used. The catalysts were characterized by SEM, XRD, BET, and ammonia adsorption. Then the catalytic performance was investigated during upgrading of rapeseed residual biomass pyrolysis vapors using this catalysts and a fixed-bed reactor in two stages. Experimental results showed that the addition of transition metals improved the catalytic selectivity towards aromatic hydrocarbons and Fe-Cu/13X zeolite catalyst was the best and had a high deoxygenation activity (from 62.45% to 20.56%), produced maximum monoaromatic hydrocarbons (of 27.45%), the oxygen content in bio-oil was reduced from 34.98 wt% to 16.06 wt%, the calorific value increased and thus the bio-oil quality was improved.